Design of a Web-based Document Management Application at the Gunungsindur District Office Bogor Regency - Safudin, Mahmud; Yulianto, Eko; Setiaji, Setiaji (International Journal of Computer and Information System (IJCIS), 2024)
Efficient and secure digital archive management is crucial in the digital era. This research aims to develop a digital archive information technology system to facilitate document search and storage while enhancing data security through user authentication and authorization. The methodology includes requirements analysis, system design, implementation, and testing. Requirements analysis was conducted to understand user needs. System design involved creating an Entity Relationship Diagram (ERD) and Logical Record Structure (LRS). Implementation used PHP and MySQL. Testing was performed using the black box method to ensure system functionality according to specifications. The results indicate improved archive management efficiency, ease of document search, and enhanced data security. The system also allows for the integration of various types of archives into a structured platform. Recommendations for further development include regular security testing, adding a disposition feature, optimizing the search algorithm, and user training.